Relationship of simple reaction time and aerobic and anaerobic capacities with performance of recreational adult orienteers - Carolina Cunha Kuhl; Thiago Emannuel Medeiros; Paulo Henrique Pauli; Marcos Vinícius Soares Martins; Marcos Roberto Queiroga; Marcus Peikriszwili Tartaruga; Mayara Maciel Batista (Universidade Federal de Santa Catarina, 2019)
This study aimed to examine the effects of Simple Reaction Time (SRT), Maximal Oxygen Uptake (O2max) and Maximal Anaerobic Power (Pmax) on the performance of category A recreational adult orienteers of both sexes. Sixteen subjects (8 men and 8 women; age: 30 ± 4 and 27 ± 5 years; body mass 78.8 ± 5.9 and 69.2 ± 10.4 kg; SRT: 1.391 ± 0.19 and 1.317 ± 0.25 ms; O2max: 67.4 ± 3.22 and 48.5 ± 8.28 ml.kg-1.min-1; Pmax: 675.0 ± 149.6 and 458.4 ± 88.62 W), were submitted to three evaluation sessions: sample characterization (1st session); SRT - Reaction Time Task v.2.0, O2max, and Pmax - Running Anaerobic Sprint Test (2nd session); official Orienteering test (3rd session). Results of comparison (Student's T-test) and relation (Pearson Product-Moment Correlation and Multiple Linear Regression) tests showed significant relationships between independent variables and performance. Pmax presented strong predictive power in the male group (41%), followed by SRT (32%) and O2max (27%). In the female group, SRT was the most predictive variable (54%), followed by O2max (32%) and Pmax (12%). These findings indicated that SRT, O2max, and Pmax are variables predictive of performance in recreational category A orienteers. Specifically in recreational orienteers with high cardiorespiratory capacities, Pmax seems to be the main predictor variable. Conversely, SRT becomes the variable with the greatest predictive power.